(untitled) (Bulletin KNOB, 2015)
During the eighteenth century there appeared a very substantial illustrated historical-topographical description of the Republic, De Tegenwoordige Staat der Vereenigde Nederlanden (The Current State of the United Netherlands, 23 vol., 1738-1803). Augmenting this was a richly illustrated serial publication, Het Verheerlykt Nederland (The Netherlands Exalted, 9 vol., 1745–1774). This article presents quantitative research into a number of basic but crucial questions regarding these publications. Which provinces featured most frequently? Were the cities the main focus of the illustrations, or did the countryside also receive some attention? Which buildings were depicted? And how old were those buildings? By answering these questions and also comparing them with three antiquarian publications by, respectively, Ludolf Smids, Hugo Franciscus van Heussen, and Mattheus Brouërius van Nidek and Isaac Le Long, an attempt is made to discover what in those days was considered worth illustrating and why. The article concludes with an exploratory study of the extent to which illustrations in eighteenth-century serial publications were consistent with or, conversely, differed from those in older historical- topographical publications. A related question is whether the illustrators relied on their own observations or on older depictions, or on both. It is clear that of all the provinces Holland, the economic, political and cultural centre of the Republic, invariably received the lion’s share of attention. How ever, interest in the countryside and the urban periphery was on the rise, especially in comparison with the seventeenth century. De Tegenwoordige Staat and Het Verheerlykt Nederland are located within the tradition of illustrated historical- topographical publications. The oldest Dutch examples featured pictures of only the most important religious and secular public buildings in a city, such as the main church and the town hall, but in the course of the seventeenth century the types of buildings illustrated expanded considerably. That trend continued in publications like De Tegenwoordige Staat and Het Verheerlykt Nederland. Although pictures of churches and town halls still figured prominently, other buildings like marketplaces, charitable institutions, (former) monasteries and abbeys, bastions, town gates, treelined canals, country houses and castles in the vicinity of the city were also frequently illustrated. Surprisingly, most of the buildings depicted in De Tegenwoordige Staat and Het Verheerlykt Nederland were quite old, dating back to the Middle Ages, while pictures of seventeenth- and eighteenth-century buildings were far rarer. The historical-topographical series differ little in this respect from comparable antiquarian publications. A building’s age must consequently have been an important criterion for both the publishers and the purchasers of historical-topographical works.